Pengembangan Seni Masamper sebagai Penguat Identitas Budaya Masyarakat Sangihe di Sulawesi Tengah - Meyltsan Herbert Maragani; Stefanny Mersiany Pandaleke; Meindelshon Yovit Patras (Program Studi Pendidikan Musik FBS UNP, 2023)
Purpose: Masamper, a traditional art of the Sangihe people singing together reciprocally, currently exists in one area in Central Sulawesi, namely in Laonggo village, Banggai district. This study aims to describe the strategy for developing Masamper art to strengthen the cultural identity of the Sangihe people in Laonggo village, Central Sulawesi. Method: The method used in this study is a qualitative method with a case study approach. Data were collected through observation, interviews and studying documents. Result and Discussion: The results of the study explain that Masamper as a traditional art of the Sangihe people in Laonggo village, Central Sulawesi, is a representation of the cultural identity of the Sangihe people, which reflects cultural similarities between fellow Sangihe people. In addition, changes in the form of implementation from entertainment activities to competition by involving other ethnic communities around Laonggo village, resulting in new forms of Masamper singing activities, is a form of adjustment as a strategy for the development & preservation of Masamper art. carried out by the Sangihe community so that masa per can be accepted. Its existence in the Central Sulawesi region can still be preserved so that the cultural identity of the Sangihe ethnic community in Central Sulawesi is getting stronger. Therefore, as a cultural identity, the Sangihe community in Laonggo village should continue to preserve Masamper by utilizing the role of informal and formal education.